Synthesis of highly fluorescent nitrogen-rich carbon quantum dots and their application for the turn-off detection of cobalt (II) - Bano D.; Kumar V.; Chandra S.; Singh V.K.; Mohan S.; Singh D.K.; Talat M.; Hasan S.H. (My University, 2025)
In this study, we have reported easy and economical synthesis of highly fluorescent nitrogen-rich carbon quantum dots (N-CQDs). The as-prepared N-CQDs displayed strong blue color emission along with CIE co-ordinate index (0.15, 0.14). The N-CQDs possess comparatively high QY of 57% using quinine sulfate as a standard. Furthermore, the as-prepared N-CQDs defend against the high salt strength and longtime photostability over the six months of incubation. Apart from this, the as-prepared N-CQDs responded as a sensor for the ‘turn-off’ detection of Co2+ along with the detection limit of 0.12 μM over a linear range from 0.5 to 3 μM. The mechanistic study proved the detection of Co2+ was based on the IFE, static quenching, aggregation, and complex formation between the amino group of N-CQDs and Co2+. Moreover, the fluorescence of the quenched N-CQDs can reappear and get ‘turn-on’ by using GSH, AA, EDTA, and cyst; thus, the prepared N-CQDs could further execute as a probe for the Co2+ detection. Inspired by these outstanding properties, the as-prepared N-CQDs were also successfully employed for the practical application toward monitoring the trace level of Co2+ in a vitamin B-12 sample. © 2019 Elsevier B.V.